The effectiveness of Electronic Resident ID Card Services at the Demographic affairs office, Civil Registration office, Labor and Transmigration office at Soppeng District - Edi Sutriadi; Dahlan Dahlan; Djamil Hasim (Jurnal Ilmiah Ilmu Administrasi Publik, 2018)
The effectiveness of an act of service or specific actions performed in a precise and impact on the fulfillment of the needs of the public. This study aims to determine the effectiveness of the service of electronic identity cards (E-ID) at the official residence, civil records, manpower and transmigration Soppeng. To achieve these objectives the researchers used a technique of collecting data through interviews, observation and documentation. Data have been obtained from the results of the study were processed using qualitative analysis. The results showed that: (1) The efficiency of service E-ID card at the Department of Population, Civil, Labor and Transmigration Soppeng less effective, (2) Procedure service E-ID card is good, (3) coordination of the leadership of subordinates at the Department Population, Civil, Labor and Transmigration Soppeng are effective, (4) The responsiveness of the employees already good, (5) Facilities and infrastructure are less effective.